Sourcebook for ancient Mesopotamian medicine - Scurlock, Jo Ann, 1953- (Writings from the ancient world, 2014)
Ancient Mesopotamia, one of the sources of our own Western medical tradition, vies with ancient Egypt for having produced the world's earliest recorded medical texts. This volume is an introductory guide to Mesopotamian medicine for readers at any level of proficiency in cuneiform. With transliterations and translations of individual tablets representing the full range of medical texts both in time (from Ur III to the Seleucid period, ca. 2112-100 BCE) and by type (diagnostic, therapeutic, and pharmacological), it offers readers a working knowledge of these very difficult but ultimately extremely informative texts. (back cover).